Congenital malformations of the genital tract (vagina agenesis) - etiological considerations - Puga C., Romulo (2015)
This is a presentation of three cases of congenital absence of vagina; two of them were women with normal uterus and ovulation who asked treatment by cyclic abdominal pain due to hematometra; the remmanent case was a male pseudohermaphrodite due to feminizing testis, The authors have treated these cases with the technique of Mc Indoe, obtaining good results; the psudohermaphrodite besides suffered gonadectomy and unterior treatment with estrogens.